Risk management and control pitfalls of local governments in Ghana - Aikins, Anthony Egyir; Mensah, John Victor; Essaw, David Wellington (Institute of Accounting Research and Novation (IARN), 2024)
Globally, local governments are required to minimise risks and adopt effective and efficient control structure to enhance delivery of public services to the people. In Ghana, some local governments record risk management and control irregularities that affect public service delivery. This paper examined the components of the risk management and control structure in four local governments in Central Region of Ghana to determine the pitfalls. The study employed a qualitative design to purposively select 14 key informants to provide primary data. They were two Internal Auditors, three Co-ordinating Directors, three Chairpersons of Audit Committees, two District Auditors, one regulator from the Central Region, and three regulators at the national level. Secondary data sources were the District Auditors’ and Auditor-General’s reports and other documents related to the study. Key informant interview and document review were the data collection methods and interview guide and document review guide were the data collection instruments. Pattern matching and content analysis were employed as the main tools for analysing the primary data. Desk review was used to analyse the secondary data. The study revealed that weak composition of the Audit Committees and management bodies’ philosophy and operating style did not help the selected local governments to provide the people’s needs to expectation